Analisis Status Keberlanjutan Ekowisata Boonpring di Kabupaten Malang Provinsi Jawa Timur - Muhammad Al Furqan Hakim; Wonny Achmad Ridman; Alla Asmara (President University, 2022)
Abstract. The economic and environmental sectors often have differences and tend to be contradictory. Ecotourism is one solution in resolving the conflict between the economy and the environment. However, if it is not managed properly, it tends to cause inequality in one of its dimensions. Purpose: to examine the sustainability status of Boonpring ecotourism through several dimensions. Methods and Results: The method for assessing sustainability status uses MDS (Multi Dimensional Scaling) with Rapfish (Rapid Apprasial Index) which is modified into Rapecotourism. The value is obtained from the attribute assessment on each dimension consisting of the ecological dimension, the economic dimension, and the human resource dimension. Sustainability parameters consist of (0-25.00%) not sustainable, (25.01-50.00%) less sustainable, (50.01-75.00%) moderately sustainable, (75.01-100%) very sustainable. Then proceed with leverage analysis to determine the sensitive attributes that play a role in determining the sustainability of a dimension. Result: The sustainability analysis of Boonpring Ecotourism shows that the ecological dimension (54.46%), the economic dimension (63.79%), and the human resource dimension (61.03%) all have sufficient sustainability values. Conclusion: Boonpring ecotourism is quite sustainable, with a note that there are several lever attributes that must be improved, such as regulations related to ecotourism management which must be ratified immediately, so that ecotourism can become very sustainable.